Prone versus Supine Position during Surgery for Supracondylar Humeral Fractures - Olcay Guler; Serhat Mutlu; Mehmet Isyar; Harun Mutlu; Halis Cerci; Mahir Mahirogullari (Journal of Orthopaedic Surgery, 2016)
Purpose To compare the supine versus prone position in closed reduction and percutaneous pinning for supracondylar humeral fractures in children in terms of patient characteristics and outcome. Methods Records of 25 girls and 31 boys aged 4 to 9 (mean, 6.7) years who underwent closed reduction and percutaneous pinning in the prone (n=27) or supine (n=29) position each by one experienced surgeon for supracondylar extension type-3 humeral fractures were reviewed. Results The prone and supine groups were comparable in terms of patient characteristics and outcome, except that anaesthesia duration was shorter in surgery performed in the supine position (46.7 vs. 37.2 minutes, p<0.001). Conclusion In surgery for supracondylar humeral fractures in children, patient position affected only the duration of anaesthesia.